Creative Natives in the Digital Age : How Digital Technology Has Revolutionized Creative Work - Kabanda, Patrick (World Bank, Washington, DC, 2016)
Digital technologies have permeated modern life, and their impact on creative work has been revolutionary. This revolution, as widely noted, has disrupted the making, distribution, and consumption of creative output. On the downside, key concerns include Internet-induced piracy and inequality. Yet digital technologies also accelerate opportunities. So, how can these opportunities be reaped to promote creative work for development? Suggestions here include closing the digital gender gap, promoting appropriate intellectual property rights, and providing digital literacy. More needs to be done to understand the benefits and limitations of digital technologies on creative work for human development.